Reflexões de um professor de biologia como estudante do Curso de Medicina da Universidade Federal de São Carlos 2018 – 2023 - Melo Junior, José Dias (Universidade Federal de São Carlos, 2023)
The development of this Undergraduate Thesis (TCC) reflects the journey of a Biology Teacher in the Public Basic Education system of the State of São Paulo, who simultaneously enrolled as a student in the Medicine Program at the Federal University of São Carlos (UFSCar). This TCC narrates the construction of a medical professional over the six years of undergraduate education, highlighting the reflections and learnings that emerged along this path. Growing up in the outskirts of Diadema, he always had the dream of pursuing Medicine. However, as there were no references in the family with a college degree, he was discouraged due to the social context in which he found himself. With the move to Hortolândia and work at the Brazilian Company of Post and Telegraph in Campinas, a new hope arose with the arrival of the preparatory course from the UNICAMP Student Directory (DCE) and the beginning of undergraduate program in Biological Sciences at UNESP Rio Claro Campus. The experience as a teacher in the State of São Paulo Basic Education system, enrollment and withdrawal from two postgraduate programs, as well as an encouraging Wife, led to the enrollment in the Medicine Program at UFSCar, once again breaking old paradigms and creating new ones in the face of society, the community, and family.
Reflections of a biology professor as a etudent of the Medicine Course at the Federal University of São Carlos 2018 – 2023
Keywords: PBL; Professor de biologia; Estudante de medicina; Biology Teacher; Medical student; CIENCIAS DA SAUDE::MEDICINA